2019
DOI: 10.1016/j.cbi.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The soluble curcumin derivative NDS27 inhibits superoxide anion production by neutrophils and acts as substrate and reversible inhibitor of myeloperoxidase

Abstract: A water-soluble curcumin lysinate incorporated into hydroxypropyl-β-cyclodextrin (NDS27) has been developed and shown anti-inflammatory properties but no comparative study has been made in parallel with its parent molecule, curcumin on polymorphonuclear neutrophils (PMNs) and myeloperoxidase (MPO) involved in inflammation. The effect of NDS27, its excipients (hydroxypropyl-β-cyclodextrin and lysine), curcumin lysinate and curcumin were compared on the release of superoxide anion by PMNs using a chemiluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…These results were in agreement with those achieved by Fu et al [ 50 ], who found that curcumin attenuated the infiltration of inflammatory cells and the activity of MPO. Also, our results are in line with Franck et al [ 65 ], who demonstrated that curcumin is a reversible inhibitor of MPO by acting as an excellent electron donor in the peroxidase cycle of the enzyme.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with those achieved by Fu et al [ 50 ], who found that curcumin attenuated the infiltration of inflammatory cells and the activity of MPO. Also, our results are in line with Franck et al [ 65 ], who demonstrated that curcumin is a reversible inhibitor of MPO by acting as an excellent electron donor in the peroxidase cycle of the enzyme.…”
Section: Discussionsupporting
confidence: 92%
“…Dilutions of the cell suspension and reagents were performed to work with a final volume of 200 µL. The superoxide anion production was measured by chemiluminescence (CL) according to Franck et al [ 25 ], but L-012 was used as a chemiluminescent probe. L-012 is a luminol analogue generally used to measure reactive oxygen and nitrogen species (RNOS) in inflammatory situations, especially superoxide anions derived from NADPH oxidase activity [ 26 ]; it is also used to detect HOCl formation resulting from MPO activity [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SIEFED assay was used as a pharmacological tool for the screening of MPO inhibitors [ 25 ]. One million mdMSCs were suspended in 1 mL HBSS and serial dilutions were performed to obtain cell suspensions ranging from 100,000 to 195 cells in 500 µL HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin also contains neuroprotective effects and are useful to treat neurodegenerative disorders (Cole et al, 2007, Abu-Taweel GM, 2016). Many studies have revealed that curcumin exhibits various antioxidant properties (Ciftci et al, 2012, Kunihiro et al, 2019, Tao et al, 2019, Franck et al, 2019, Chaudhary et al, 2019, Mukherjee et al, 2019, Wu et al, 2019). In general, commercially available curcumin contains approximately 3% bisdemethoxycurcumin, 17% de- methoxycurcumin and 77% curcumin (Abu-Taweel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%